2016
DOI: 10.1038/srep25250
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis of relationship between landscape pattern and urban river water quality in different seasons

Abstract: Water quality is highly dependent on the landscape characteristics. In this study, we investigated the relationships between water quality and landscape pattern (composition and configuration) in Huzhou City, China. The water quality variables, including pH, dissolved oxygen (DO), chemical oxygen demand (CODMn), Biochemical Oxygen Demand (BOD), NH3-N, petroleum, dissolved total phosphorus (DTP), and total nitrogen (TN) in low water, normal water and flood periods were identified by investigating 34 sampling si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 36 publications
1
61
0
1
Order By: Relevance
“…The land use composition within each of these buffer widths was calculated for analysis. We took a circular area surrounding the measurement point and determined the land use composition within different buffer zone widths to the specific monitoring point (Guo et al 2009, Xiao et al 2016. Annual mean water quality indicators were calculated for the analysis of the relationship between land use composition and water quality.…”
Section: Analysis Of the Effect Of Buffer Zone Widthmentioning
confidence: 99%
“…The land use composition within each of these buffer widths was calculated for analysis. We took a circular area surrounding the measurement point and determined the land use composition within different buffer zone widths to the specific monitoring point (Guo et al 2009, Xiao et al 2016. Annual mean water quality indicators were calculated for the analysis of the relationship between land use composition and water quality.…”
Section: Analysis Of the Effect Of Buffer Zone Widthmentioning
confidence: 99%
“…Forest land use was most often negatively linked with degraded water quality [55,73]. Few studies have shown that forest land cover has a positive relation with nitrogenous materials [47,74,75]. It could be attributed to higher water discharge and lower water residence time, which affects the uptake capacity of vegetation [63].…”
Section: Impacts Of Terrestrial Determinants On Cewqmentioning
confidence: 99%
“…However, the median value was convincing enough and representative of the given water-climate system for a macroscale study, when the trends were not significantly large. Results of trend analysis at the Mekong, Murray and Yukon, watersheds are shown on independent variables which make the strongest linkage with precipitation and temperature elasticity of water quality parameters [47]. Correlation and SMLR gave an idea about linear relations.…”
Section: Trends Analysis Of Water Quality Parameters and Climatic Drimentioning
confidence: 99%
See 1 more Smart Citation
“…Remote densing data are used to monitor vegetation and distinguish anthropic events 10 Vegetation indexes are based on linear combinations of spectral data, enhancing vegetation presence 11 . The normalized difference vegetation index (NDVI) emphasizes variations of band density for environmental analysis with conclusions based on the vegetal cover dynamics 12 .…”
Section: Introductionmentioning
confidence: 99%